Parental Influence on Career Choices of Navrongo Senior High School Students in the Kassena-Nankana Municipality - Anovunga, Alfred Alunga (Innovare Journal of Education, 2023)
This study examined parental influence on the career choices of Navrongo Senior High School students in the Kassena-Nankana Municipality. The study sought to assess parental factors that contribute to the career choice of Navrongo Senior High School students in the Kasena Nankana Municipality, examine the effects of parental influence on the career choice of their children in Navrongo Senior High School, and find out the strategies that Navrongo Senior High School can adopt to assist students make informed career choice. Participants included in this study were 150 senior high school students. Stratified and simple random sampling techniques were used to select the sample size. Both open-ended and closed Likert Scale questionnaires were used for data collection. Percentages, bar charts, pie charts, and standard deviations were used to present the results. The result indicated that parents, in one way or the other, do influence their children in choosing careers. From the study, the respondents believed that when parents choose careers for their children, they do not enjoy their lifelong vocation. It was therefore recommended that the school solicit parents’ views when organizing career guidance for students, and parents should also be made aware of the negative consequences of their actions when they impose their opinions on their children when planning for their careers. Again, career programs should be introduced in Senior High Schools to assist students in making appropriate career choices.